Extracellular compartments in matrix morphogenesis: collagen fibril, bundle, and lamellar formation by corneal fibroblasts (The Rockefeller University Press, 1984)
The regulation of collagen fibril, bundle, and lamella formation by the corneal fibroblasts, as well as the organization of these elements into an orthogonal stroma, was studied by transmission electron microscopy and high voltage electron microscopy. Transmission and high voltage electron microscopy of chick embryo corneas each demonstrated a series of unique extracellular compartments. Collagen fibrillogenesis occurred within small surface recesses. These small recesses usually contained between 5 and 12 collagen fibrils with typically mature diameters and constant intrafibrillar spacing. The lateral fusion of the recesses resulted in larger recesses and consequent formation of prominent cell surface foldings. Within these surface foldings, bundles that contained 50-100 collagen fibrils were formed. The surface foldings continued to fuse and the cell surface retracted, forming large surface-associated compartments in which bundles coalesced to form lamellae. High voltage electron microscopy of 0.5 micron sections cut parallel to the corneal surface revealed that the corneal fibroblasts and their processes had two major axes at approximately right angles to one another. The surface compartments involved in the production of the corneal stroma were aligned along the fibroblast axes and the orthogonality of the cell was in register with that of the extracellular matrix. In this manner, corneal fibroblasts formed collagen fibrils, bundles, and lamellae within a controlled environment and thereby determined the architecture of the corneal stroma by the configuration of the cell and its associated compartments.